Ayyankali : a dalit leader of organic protest - Nisar, M. (Other Books, 2007)
Pulayars, one of the many Dalit communities in Kerala, were ordered to keep at a distance of ninety-six steps away from a Brahmin, not allowed to cover themselves above the waist or below the knees, denied admission to public roads and subjected to endless oppression. Besides, they were bought and sold as slaves even up to the middle of the nineteenth century. Ayyankali (1863-1941), one of the foremost Dalit leaders, challenged these brutal caste codes.This book chronicles his organic protest in Travancore and provides a critical analysis of the social reform movements in Kerala under the colonial rule. It seeks answers to a lot of questions: How did the various reformist organizations disintegrate into instruments of caste consolidation? How did western education and colonial modernity affect the orthodox setup? What was the role of the middle class in the development of community formation? Why did the so-called reform movement refuse to bother itself with the problems of the poor, the women and the Dalits? How did the Dalits, who were inferiorized and oppressed, react to these changes? What fuelled the emergence of Dalit leadership? What were the changes brought about in the social landscape of Kerala by Ayyankali’s movement?